Case report: Limb-sparing surgery of tibial chondrosarcoma with frozen autologous bone graft using liquid nitrogen in a dog - Shimada, Masakazu; Nagashima, Tomokazu; Michishita, Masaki; Yazawa, Daisuke; Hara, Yasushi (Frontiers in Veterinary Science, 2023)
Chondrosarcoma is the second most common primary bone tumor after osteosarcoma in dogs. Chondrosarcoma has a good prognosis owing to its low metastatic rate and long survival time, even with amputation alone. However, amputation risks reducing the quality of life in patients with other orthopedic diseases of the non-affected limb, neurological diseases, or large body size. Limb-sparing surgery with frozen autologous bone grafting using liquid nitrogen allows bone quality to be maintained in the normal bone area while killing tumor cells, thereby preserving the affected limb. Thus, it is expected to maintain the quality of life. We describe herein limb-sparing surgery for tibial chondrosarcoma with frozen autologous bone graft using liquid nitrogen in an 8-year and 8-month-old castrated male bulldog weighing 29.2 kg. The patient had chondrosarcoma of the left tibia, suspected cranial cruciate ligament rupture of the right stifle, and degenerative lumbosacral stenosis. In such a case, amputation would increase the burden on the non-affected limb or spine, which could cause difficulty in walking; therefore, we performed limb-sparing surgery. Postoperatively, although a circumduction gait associated with stifle arthrodesis remained, the patient maintained the quality of life for 20 months, and the owner was satisfied with the results.